Novel reusable functionalized magnetic cobalt ferrite nanoparticles as oil adsorbents - Ajra Hadela; Marijana Lakić; Mateja Potočnik; Aljoša Košak; Andreja Gutmaher; Aleksandra Lobnik (Adsorption Science & Technology)
Magnetic nanoparticles are amongst the most promising adsorption materials for oil spill clean-up due to their high surface area, ease of functionalization with high oil affinity and facile separation after the cleaning process with an external magnetic field. In this work, we successfully synthesized magnetic cobalt ferrite nanoparticles (CoFe 2 O 4 NPs) that were electrostatically stabilized and functionalized with various alkoxysilanes for effective oil adsorption and oil spill removal. Additionally, the adsorption capacity of CoFe 2 O 4 NPs was determined, and the possibility of their reuse assessed. Prepared samples showed high oil adsorption capacities between 2.6 and 3.5 g of oil per g of nanoparticles and were successfully collected with an external magnet. Furthermore, the samples showed excellent properties after regeneration, as their adsorption capacity decreased by less than 3% after reuse. All the prepared samples were thoroughly characterized to better understand their behaviour and the differences in the use of various silanes were highlighted.